Liability Principles of PT. Perusahaan Listrik Negara (Persero) To the Loss of Consumers Electric Services - Riono Riono (Universitas Wijaya Kusuma Surabaya, 2020)
Electricity is essential for our daily needs and community and businesses because it can run their products. Recently the community and we depend on electricity, so the usage of electricity is getting an increase. All our hardware and software tools use electricity because electricity changes our style in daily life. So, the management of electricity which the State gives to PT. Perusahaan Listrik Negara (PLN) is a